SYNTHESIS AND ANTIMALARIAL EVALUATION OF 1-(2,4- DIMETHOXYPHENYL)-3-(4-TRIFLUORO METHYL-PHENYL) PROPAN-2-ENE-1- ONE - HAMZA, A. N; IDRIS, A.Y; MUSA, A.M; OLORUKOOBA, A.B (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Malaria is one of the most serious health problems worldwide and Its treatment has been compromised by drug resistance. Chalcones represent an important chemical scaffold with promising antimalarial activity. A chalcone derivative; 1(2,4dimethoxyphenyl)-3-(4-trifluoro methyl-phenyl) propan-2-ene-1-one (Compound P21) was synthesized by modified ClaisenSchmidt condensation reaction. The structure of compound P21 was established using Fourier transform infrared (FT-IR), proton and carbon-13 nuclear magnetic resonance (NMR) spectroscopy, and also mass spectrometry (MS). The compound was screened for in-vivo antimalarial activity in mice infected with P berghii parasite, using curative model. Compound P21 displayed appreciable activity (66% parasitaemia suppression) comparable to that of chloroquine (5 mg kg-1) at a dose of 175mg kg-1 in the curative test (p<0.05). The present finding suggests that compound P21 is a promising antimalarial compound and is a candidate for further optimization and evaluation.